High gene flow maintains wide-range species cohesion in a Neotropical epiphyte (Tillandsia aeranthos, Bromeliaceae) - Aoki-Goncalves, Felipe [UNESP]; Dantas De Queiroz, Marcos Vinicius [UNESP]; Guimaraes, Thais De Beauclair; Neffa, Viviana Solis; Palma-Silva, Clarisse (Oxford Univ Press, 2020)
Studies of patterns of genetic diversity, genetic structure and ecological data across geographical ranges of species allow us to test hypotheses about the evolutionary responses of organisms to fluctuations in habitat connectivity and availability. Here we present a study aiming to assess genetic diversity, population structure and breeding system across the geographical distribution of a subtropical epiphyte, Tillandsia aeranthos (Bromeliaceae), endemic to the Plata River basin (Pampa biome). Seven nuclear microsatellite markers were genotyped in 203 individuals from 13 localities across Brazil and Argentina and 14 plastid regions were sequenced for a subset of the individuals. Additionally, we performed controlled pollination experiments to discuss correlations between breeding system, genetic diversity and structure in the species. Nuclear diversity levels were high (H-E = 0.806, H-o = 0.745, allelic richness = 5.860) with no haplotype differentiation detected (c. 9 kpb sequenced). Bayesian assignment analysis, supported by principal coordinate analysis and analysis of molecular variance, show low genetic structure across the studied area (F-ST = 0.031, P < 0.001). Controlled pollination experiments indicated complete self-incompatibility in all localities analysed. Our results show effective gene flow maintaining low genetic structure between localities for T. aeranthos across an extensive area in the Pampa.
Keywords: breeding system; microsatellites; southern Brazil; population genetics